Development of an Assessment Instrument to Measure High School Students' Collaboration Skills in Physics Learning - Simamora, Nadia Natalia; Istiyono, Edi; Wilujeng, Insih (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2024)
This study aims to determine the feasibility of the instrument for assessing students' collaboration skills in learning physics. This research is Research and Development (R & D) research with the Analysis, Design, Development, Implementation and Evaluation (ADDIE) model. In this research, the researcher limited the stages in the ADDIE model to the development stage only, so that the development research stages were reduced from five steps to three steps, namely analysis, design and development. The population in this study were students of SMA Negeri 1 Piyungan with a sample of 25 students. The instrument used is a questionnaire. The data obtained were analyzed using validity and reliability tests with the help of the SPSS application. The results obtained show that the validity value obtained is 1.00 with a very high validity category and the reliability value shown through the Cronbach's Alpha value of 0.927 is in the very high criteria. In the small group trial, an rtable value of 0.396 was also obtained, and the rcount value was in the range of 0.425 – 0.760. From these results it shows that the instrument for assessing students' collaboration skills in learning physics is valid and feasible to use.